Degradation of phenol from aqueous solution using waste blast furnace flue dust and hydrogen peroxide. Issue 21 (2nd May 2016) - Zeng, Danlin; Liu, Shenglan; Zhang, Qi; Wang, Guanghui; Chen, Yang; Tian, Yongsheng
Abstract: A novel method to degrade phenol from simulated wastewater was studied using waste blast furnace flue dust with hydrogen peroxide (H2 O2 ). The factors that affect the degradation efficiency, including the pH of the solution, the initial H2 O2 concentration, the amount of blast furnace flue dust, the reaction temperature, and the reaction time, were studied. The experimental results show that 1, 000 mg/L of phenol in simulated wastewater can be decomposed completely within 12 h by 15 g/L blast furnace flue dust with 30 mmol/L H2 O2 in a solution whose pH was 3.0 at the temperature of 35°C. The mechanism of phenol degradation was also investigated by high-performance liquid chromatography, X-ray diffraction, and UV–vis spectrum.